Testing of a pond‐side molecular diagnostic tool for the detection of white spot syndrome virus in shrimp aquaculture. Issue 1 (26th September 2018) - Minardi, Diana; Bateman, Kelly S.; Kuzdzal, Agnieszka; Stone, Michelle; Avant, Justin; Condliffe, Richard; Brotherton, Paul; Laverick, Mark; Sritunyalucksana, Kallaya; Itsathitphaisarn, Ornchuma; Baoprasertkul, Puttharat; Stentiford, Grant D.
Abstract : White spot disease in penaeid shrimp is caused by the white spot syndrome virus (WSSV). It is the most economically important disease of farmed warm‐water shrimp, causing extensive economic losses estimated from $8 to $15 billion since its emergence in the 1990s. Early diagnosis of disease is critical in the management of outbreaks and to avoid crop losses. Diagnosis of white spot disease is generally carried out in centralized laboratory settings using molecular biology approaches. However, this mode of testing can be expensive and time consuming, requiring laboratory equipment, highly trained laboratory personnel, dedicated laboratory space, and long‐distance transportation of samples from field to lab. In‐field diagnostics are gaining credence as tools for rapid and early animal disease detection, allowing diagnosticians and farmers to potentially manage disease outbreaks from the pond side. In the present study, we describe the development and application of a new in‐field point‐of‐need diagnostic test and platform for the diagnosis of WSSV in remote settings (shrimp farms). We report its performance in laboratory and field settings and compare it with current gold‐standard diagnostic approaches. We discuss the potential benefits (and barriers to uptake) of applying such testing in the global shrimp farming sector.